A cross-cultural perspective about the Ripple effect of corporate social responsibility on internal brand commitment through corporate reputation - Junça Silva, A.; Guilherme, M. (Corporate Social Responsibility and Environmental Management, 2025)
This study, grounded in social identity theory, aimed to examine the mediating role of corporate reputation in the relationship between corporate social responsibility (CSR) and internal brand commitment. Additionally, it sought to investigate whether individualistic versus collectivistic cultural orientations moderate this indirect relationship. This research consisted of two complementary studies. The first study employed a qualitative approach, utilizing interviews to explore employees' perceptions of CSR practices (N = 14). The second study adopted a quantitative approach, using an online survey to collect data from 506 participants distributed across Portugal (a collectivistic culture) and France, Italy, and Spain (characterized as individualistic cultures). The findings from the first study revealed that employees perceive CSR practices as enhancing an organization's reputation. Additionally, these practices are seen as positively influencing employees' performance, job satisfaction, and commitment by boosting their morale and strengthening their sense of organizational identification. The results from the second study showed that CSR improved employees' internal brand commitment through increases in corporate reputation. It also demonstrated that the degree of individualism or collectivism affected how employees perceived the organization's reputation and influenced their internal brand commitment. Finally, it was also shown that national culture moderated the indirect effect of CSR on internal brand commitment through corporate reputation, in such a way, that this relationship was stronger in collectivistic countries (versus individualistic). The present study contributes to reinforcing the importance of adapting CSR initiatives to the national culture, as a strategy to improve employees' commitment toward their brand.